PENGARUH PENERAPAN RUANG KOSONG PADA LUBANG LEDAK TERHADAP JARAK LEMPARAN BATU TERBANG < 150 M GUNA MEMPERKECIL JARAK EVAKUASI ALAT MEKANIS (STUDI KASUS PELEDAKAN PADA PT ALAMJAYA BARA PRATAMA) - Wanda Adinugraha; Abdillah Fikri (PPSDM Geominerba, 2022)
Based on the blasting analysis with air decking on the distance of flying rock throws, there are three parameters of blasting geometry that affect flying rock throws, namely the height of the water deck column, the height of the stemming column, and the initial burden distance. Based on the standard deviation value, the calculation of the predicted distance of flying rock throws uses the theory of Richard and Moore's cratering type, resulting in a prediction of the distance of flying rock throws that are close to the actual distance of Flying Rock throws. In order to distance the flying rock <150 m, the recommendation for blasting geometry at the initial burden minimum is 3.25 m and maximum is 4 m and the height of the stemming column is added 0.65 m from the actual stemming height and height the air deck column is reduced by 0.65 m from the actual air deck height.